Laboratory leaching tests to study the effects of post-treatment storage periods on CCA leachability and fixation in treated permeable and refractory Malaysian hardwoods - Andrew H. H., Wong; H. C, Lai (Universiti Malaysia Sarawak, (UNIMAS), 2006)
37th Annual Meeting of theInt'l Research Group on wood Protection, 18022 June 2006, Tromso, Norway.